Experimental investigation of pulse‐type ground motion effects on a steel building with nonlinear viscous dampers. (2nd September 2021) - Dong, Baiping; Ricles, James M.; Phillips, Brian M.
Abstract: Near‐fault pulse‐type ground motions have characteristics that are substantially different from ordinary far‐field ground motions. It is essential to understand the unique effects of pulse‐type ground motions on structures and include the effects in seismic design. This paper investigates the effects of near‐fault pulse‐type ground motions on the structural response of a 3‐story steel structure with nonlinear viscous dampers using the real‐time hybrid simulation (RTHS) testing method. The structure is designed for 75% of the code‐specified design base shear strength. In the RTHS, the loop of action and reaction between the experimental and numerical partitions are executed in real time, accurately capturing the velocity pulse effects of pulse‐type ground motions. A set of 10 unscaled pulse‐type ground motions at the design basis earthquake (DBE) level is used for the RTHS. The test results validated that RTHS is a viable method for experimentally investigating the complicated structural behavior of structures with rate‐dependent damping devices, and showed that the dampers are essentially effective in earthquake hazard mitigation effects involving pulse‐type ground motions. The average peak story drift ratio under the set of pulse‐type ground motions is 1.08% radians with a COV value less than 0.3, which indicated that structural system would achieve the ASCE 7–10 seismic performance objective for Occupancy Category III structures under the DBE level pulse‐type ground motions. Additionally, a nonlinear Maxwell model for the nonlinear viscous dampers is validated for future structural reliability numerical studies involving pulse‐type ground motions.